2015
DOI: 10.1002/adhm.201500273
|View full text |Cite
|
Sign up to set email alerts
|

A Near Infrared Light Triggered Hydrogenated Black TiO2 for Cancer Photothermal Therapy

Abstract: White TiO2 nanoparticles (NPs) have been widely used for cancer photodynamic therapy based on their ultraviolet light-triggered properties. To date, biomedical applications using white TiO2 NPs have been limited, since ultraviolet light is a well-known mutagen and shallow penetration. This work is the first report about hydrogenated black TiO2 (H-TiO2 ) NPs with near infrared absorption explored as photothermal agent for cancer photothermal therapy to circumvent the obstacle of ultraviolet light excitation. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
220
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(227 citation statements)
references
References 52 publications
7
220
0
Order By: Relevance
“…Oxygen vacancies are undetectable in most white TiO 2 nanomaterials, while oxygen vacancy is considered to be one of the feature defects in most black TiO 2 nanomaterials. Electron paramagnetic resonance (EPR) or electron spin resonance (ESR) spectroscope [37][38][39][40]52], Raman spectroscope [9,16,32,[53][54][55], and X-ray diffractometer [23,32,55] [30,33,37,41,52,55,57,59,60].…”
Section: Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxygen vacancies are undetectable in most white TiO 2 nanomaterials, while oxygen vacancy is considered to be one of the feature defects in most black TiO 2 nanomaterials. Electron paramagnetic resonance (EPR) or electron spin resonance (ESR) spectroscope [37][38][39][40]52], Raman spectroscope [9,16,32,[53][54][55], and X-ray diffractometer [23,32,55] [30,33,37,41,52,55,57,59,60].…”
Section: Defectsmentioning
confidence: 99%
“…It is likely that surface oxygen vacancies are responsible for the enhanced photocatalytic activity [39,70,75], while bulk oxygen vacancies act as trap states and charge carrier recombination centers [76]. Studies also showed that surface Ti 3+ defects could enhance hole trapping and thus facilitate the separation of photo-excited electrons and holes [57], while bulk Ti 3+ sites acted as charge annihilation centers, leading to enhanced nonradiative recombination and shorter lifetime of electrons and holes [57,60]. In addition, Ti 3+ ions with oxygen vacancies can improve the electrical conductivity of TiO 2 [73,77], which may enhance the charge transport and charge-transfer reaction [73].…”
Section: Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[80,81] Hydrogenated TiO 2 nanoparticles have recently been demonstrated with promising medical application due to their extended absorption in the infrared region. [82,83] They can efficiently convert the near-infrared light energy into thermal energy and produce localized heat island. [82] After they are injected near the cancer cells and irradiated with near-infrared light, the locally produced heat can effectively kill the cancer cells without affecting the adjacent healthy cells.…”
Section: Functional Oxides Prospective Articlementioning
confidence: 99%
“…[82,83] They can efficiently convert the near-infrared light energy into thermal energy and produce localized heat island. [82] After they are injected near the cancer cells and irradiated with near-infrared light, the locally produced heat can effectively kill the cancer cells without affecting the adjacent healthy cells. [82] This process is named as photothermal therapy.…”
Section: Functional Oxides Prospective Articlementioning
confidence: 99%